FSCS Reveals the Complexity of Lipid Domain Dynamics in the Plasma Membrane of Live Cells - Nicovich, Philip R; Kwiatek, Joanna M; Ma, Yuanqing; Benda, Aleš; Gaus, Katharina (Biophysical journal, 2018)
The coexistence of lipid domains with different degrees of lipid packing in the plasma membrane of mammalian cells has been postulated, but direct evidence has so far been challenging to obtain because of the small size and short lifetime of these domains in live cells. Here, we use fluorescence spectral correlation spectroscopy in conjunction with a probe sensitive to the membrane environment to quantify spectral fluctuations associated with dynamics of membrane domains in live cells. With this method, we show that membrane domains are present in live COS-7 cells and have a lifetime lower bound of 5.90 and 14.69 ms for the ordered and disordered phases, respectively. Comparisons to simulations indicate that the underlying mechanism of these fluctuations is complex but qualitatively described by a combination of dye diffusion between membrane domains as well as the motion of domains within the membrane.
Keywords: Cell Survival; buněčná membrána; membránové lipidy; kvartérní amoniové sloučeniny; fluorescenční spektrometrie; Cercopithecus aethiops; Chlorocebus aethiops; COS Cells; Quaternary Ammonium Compounds; Spectrometry, Fluorescence; COS buňky; Animals; Cell Membrane; Membrane Lipids; zvířata; viabilita buněk; benzoxaziny; Benzoxazines